The adoption and impact of food safety measures on smallholder dairy farmers’ economic welfare: Evidence from the Indo-Gangetic plains of India. - Katoch, Sonali; Kumar, Anjani; Kolady, Deepthi E.; Sharma, Kriti (International Food Policy Research Institute, 2024)
This study examines the adoption of compliance with food safety measures (FSM) using cross-sectional data collected at the farm level in three key states of the Indo-Gangetic Plains, Bihar, Punjab, and Uttar Pradesh in 2023. A Food Safety Index (FSI) was developed to assess the intensity of adoption of food safety practices. Determinants of compliance with practices were assessed using multiple linear regression and an ordered logistic model. Generalized propensity score matching was used to evaluate the heterogenous impact of the adoption of FSM on farm-level performance indicators. The findings indicate that farmers are embracing a moderate level (0.48–0.58) of the food safety index at the farm level. The various socioeconomic and demographic factors influence compliance with FSM which include education, income, marketing channel, training exposure, awareness level, and infrastructure. The impact assessment reveals the direct relationship between FSM compliance and performance indicators. However, a lower level of compliance may not yield significant improvements. The study suggests incentivization through pricing reforms, improving infrastructure, and strengthening formal marketing channels.